RATS TRAPPING AT DIFFERENT TYPES OF LOCATION IN LIWA BOTANICAL GARDEN, LAMPUNG, INDONESIA - Novera, Bernice Rizki; Kanedi, M.; Nurcahyani, Nuning; Sutyarso (International Journal of Research -GRANTHAALAYAH, 2020)
Motivation/Background: Rat is cosmopolitan animal which means they can live in all type of places worldwide, including highlands, lowlands, rice fields, forests, and settlements. A high rat population can have an impact on losses in various fields of human life. The Liwa Botanical Garden is one of the areas developed for tourism so the presence of rats is important to note. Method: This study aims to determine the success rate of rat catching in Liwa Botanical Garden by different type of trapping location, namely bamboo groves, houses, river banks, and gardens. The traps were set every day for 10 days. The observations included the number of individual, the type of rat, sex and size of the trapped mice. All the data obtained were analyzed descriptively. Results: The live trapping resulted in 11 individuals of small mammals belongs to three species namely Rattus exultant, Hylomys suillus and Suncus murinus. Among the four trapping location, bamboo groves is the place that catches the most, and the females were trapped more than the males.